An Engineered Escherichia coli Strain with Synthetic Metabolism for in‐Cell Production of Translationally Active Methionine Derivatives. (13th October 2020) - Schipp, Christian Johannes; Ma, Ying; Al‐Shameri, Ammar; D'Alessio, Federico; Neubauer, Peter; Contestabile, Roberto; Budisa, Nediljko; di Salvo, Martino Luigi
Abstract: In the last decades, it has become clear that the canonical amino acid repertoire codified by the universal genetic code is not up to the needs of emerging biotechnologies. For this reason, extensive genetic code re‐engineering is essential to expand the scope of ribosomal protein translation, leading to reprogrammed microbial cells equipped with an alternative biochemical alphabet to be exploited as potential factories for biotechnological purposes. The prerequisite for this to happen is a continuous intracellular supply of noncanonical amino acids through synthetic metabolism from simple and cheap precursors. We have engineered an Escherichia coli bacterial system that fulfills these requirements through reconfiguration of the methionine biosynthetic pathway and the introduction of an exogenous direct trans‐sulfuration pathway. Our metabolic scheme operates in vivo, rescuing intermediates from core cell metabolism and combining them with small bio‐orthogonal compounds. Our reprogrammed E. coli strain is capable of the in‐cell production of l ‐azidohomoalanine, which is directly incorporated into proteins in response to methionine codons. We thereby constructed a prototype suitable for economic, versatile, green sustainable chemistry, pushing towards enzyme chemistry and biotechnology‐based production. Abstract : Doing things differently : We have metabolically engineered an E. coli strain by reconfiguring the methionine biosynthetic pathway to create a bacterial system with a trans‐sulfuration pathway for in‐cell production and incorporation of l ‐azidohomoalanine. Our system is focused on green, sustainable chemistry, and only requires water, salts, trace elements, and simple carbon sources, pushing towards enzyme chemistry and biotechnology‐based production.